Analisis Percepatan Waktu Menggunakan Metode Crashing dengan Penambahan Jam Kerja Tiga Jam dan Sistem Shift - Aulia Sivani; Elvira Handayani; Dwitya Okky Azanna; Annisaa Dwiretnani; Riki Saputra; Rioni Rizki Aldiansyah (Jurnal Talenta Sipil, 2026)
During the construction process of a project, many unexpected events can occur, one of which is project delays. These delays may result from various factors such as unfavorable weather conditions, design changes, planning errors, and several others. Therefore, it is necessary to consider alternative strategies to support project acceleration. These alternatives may include extending working hours, using more productive equipment, increasing the number of workers, utilizing materials that are quicker to install, and implementing faster construction methods. This study analyzes the acceleration of project completion time in the construction project of SMPN 3 using the crashing method, with two alternatives: extending working hours by three hours and implementing a shift system. The objective of this research is to determine the total project duration after applying crashing with the two alternatives and to identify which critical path activities were accelerated in the SMPN 3 construction project. Based on the analysis, the total project duration after crashing using the three-hour extended workday alternative is 175 days, representing a time savings of approximately 20% compared to the normal duration of 218 days. Meanwhile, the total project duration after crashing using the shift system alternative is 109 days, resulting in a time savings of approximately 50% from the original duration of 218 days.